Thiophene Ring-opening Reactions III: One-Pot Synthesis and Antitumor Activity of 1,3,4-Thiadiazoline–Benzothiazolo[3,2-b]pyridazine Hybrids† - Abdullah, Ahmad H.; Zahra, Jalal A.; Sabri, Salim S.; Awwadi, Firas F.; Abadleh, Mohammed M.; Abdallah, Qasem M.; El-Abadelah, Mustafa M. (Current Organic Synthesis, 2022)
Introduction: The preparation of model 6-chloro-5-nitrothieno[2,3-c]pyridazines incorporating (2'-halo-5'-nitrophenyl) entity is described. Interaction of these substrates with N'-(aryl)benzothiohydrazides, in the presence of triethylamine, followed a formal [4+1] annulation, furnishing the respective 1,3,4-thiadiazoline–benzothiazolo [3,2-b]pyridazine hybrids directly. This one-pot synthesis implies thiophene ring-opening and two consecutive intramolecular cyclizations. The structures of the synthesized new hybrids are supported by MS, NMR, and IR spectral data and further confirmed by single-crystal X-ray diffraction. These hybrids exhibit antiproliferative activity with notable selectivity against solid tumor cell lines (IC50: 4-18 μM). Aims: This study aimed at exploring the scope and applicability of thiophene ring-opening reaction towards the synthesis of new thiadiazoline–[fused]tricyclic conjugates. Background: α-Chloro-β-nitrothienopyridazine underwent ring-opening upon reacting with N'-(aryl)benzothiohydrazides generating 1,3,4-thiadiazoline–benzothiazolo[3,2-b]pyridazines. Objective: This new thiophene ring-opening reaction is applied to the one-pot synthesis of thiadiazoline–benzothiazolo[3,2-b]pyridazine couples. Method: A direct interaction of α-chloro-β-nitrothienopyridazine with N'-(aryl)benzothio-hydrazide at room temperature for 1-2 h occurred. Result: a-Chloro-β-nitrothieno[2,3-c]pyridazines are suitable substrates for the facile synthesis of thiadiazoline–benzothiazolo[3,2-b]pyridazine hybrids. Conclusion: This novel ring-opening reaction proceeds via formal [4+1] annulation and provides a versatile approach to various conjugated and/or fused five-membered heterocycles.
Keywords: 1; 3; 4-thiadiazoline-[fused]tricyclic hybrids